2009
DOI: 10.1266/ggs.84.233
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the Q locus in wheat by a simple PCR-RFLP method

Abstract: The Q locus located on the long arm of chromosome 5A is a key factor in evolution and widespread cultivation of domesticated wheat. The Q locus pleiotropically affects many agronomically important traits including threshability, glume shape and tenacity, rachis fragility and others. Genotyping of the Q locus based on the complex traits is ambiguous due to their multi-genetic control through interactions with the Q locus. To determine the Q locus genotype of wheat accessions possessing A genome, we developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…The genotype at the q locus was also confirmed using restriction site polymorphisms as previously reported (Asakura et al, 2009). Three intragenic regions were amplified using q-specific primers, and then the amplified products were digested with MspI, TaqI or MboI.…”
Section: Genotyping and Construction Of A Linkage Mapmentioning
confidence: 96%
See 2 more Smart Citations
“…The genotype at the q locus was also confirmed using restriction site polymorphisms as previously reported (Asakura et al, 2009). Three intragenic regions were amplified using q-specific primers, and then the amplified products were digested with MspI, TaqI or MboI.…”
Section: Genotyping and Construction Of A Linkage Mapmentioning
confidence: 96%
“…Three intragenic regions were amplified using q-specific primers, and then the amplified products were digested with MspI, TaqI or MboI. After separation of the digested fragments by electrophoresis through a 2% agarose gel and staining with ethidium bromide, the presence or absence of the three restriction sites was determined with reference to the previous data (Asakura et al, 2009). …”
Section: Genotyping and Construction Of A Linkage Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP2299 seems to be closely related to the occurrence of domesticated free-threshing wheat. The restriction enzyme MboI can be used to differentiate between Q and q at this position (Asakura et al 2009). Plant breeders use both, cultivated and wild species, to select favorable new traits in elite cultivar candidates.…”
Section: Pyrosequencing and Breeding Applicationsmentioning
confidence: 99%
“…Simons et al (2006) showed that one variation in the DNA sequence of exon 8 leads to the amino acid substitution Valine (5Aq allele) to Isoleucine (5AQ allele), which seems to be closely related to the domestication of free-threshing wheat. Recently, Asakura et al (2009) used a PCR based CAPS marker assay to genotype the 5AQ locus. Since the Q (5A chromosome) and q gene sequences (5B and 5D chromosomes) are available (Simons et al 2006;Ning et al 2009), it is now possible to align the homoeoalleles from each genome including the primitive allele 5Aq and design differentiating pyrosequencing primers.…”
Section: Introductionmentioning
confidence: 99%